Implementation of Distributive Justice as Provisioned in the Constitution of Nepal - Rai, Prithvi Nath; Chamling, Merrysha (Journal of Contemporary Review, 2024)
The Latin form of the term "Justice" is 'Justus' or 'Justia' and it is from these terms that the word jus is derived having varying meanings such as truth, morality, righteousness, equality, and fairness, mercy, impartiality, rightness, law, etc. The literal meaning of the term "Justice" indicates the fair treatment of the people. It also relates to the fair and proper administration of law and social order. Justice is not only concerned about the subject of jurists but also center philosophy of moral and social philosophy. It is the first virtue of social institutions, as truth is the systems of thought. It is believed that intrinsic justice of their actions is something that develops naturally within political communities. It is unequivocally believed that justice is the highest virtue of mankind. Without justice, there may not be peace, tranquility, prosperity, security, humanity and meaningful life in individual, family, society and nation. The absence of just has been the root cause of each conflict. Such conflict may arise from family, community, culture, economy, politics, etc. In the present scenario, there are many instances of various strifes in our society and the entire nation. All the people are suffering from different kinds of economic anomalies, societal disharmony, political unaccountability, discrepancies, irregularities and various forms of corruption. Due to all these reasons, people have been victimized by injustice. As injustice anywhere, there is a threat to justice everywhere. To explore more about hidden root causes of injustice, the research topic has been chosen to justify in all ways by interconnecting with the contemporary issues of the society and nation. The term justice is the vaguest relative term or variable which becomes coalesced with the truth from the different philosophical perspectives, economic determinative factors, political identity, religious values, socio-cultural recognition, and the like. As the truth changes; so, does the justice. Nothing is permanent in the world. Even the environment changes at its own pace, let alone other superstructures. Due to all those multifarious phenomena, the concept of justice is also found to have been understood relatively and its cycle keeps on moving accordingly as it was in the past, as it is in this present and shall be in the future too accordingly. It is associated with the pursuit of justice in the Republic commences when the elderly, wealthy Cephalus suggests that justice involves nothing more than telling the truth and repaying one’s debts.